Survival of human cadaver skin on severe combined immune deficiency pigs: Proof of concept. Issue 4 (19th March 2019) - Singer, Adam J.; Tuggle, Christopher; Ahrens, Amanda; Sauer, Mary; McClain, Steve A.; Tredget, Edward; Rosenberg, Lior
Abstract: Transplantation of human xenografts onto immunocompromised mice is a powerful research tool for studying wound healing. However, differences in healing between humans and mice and their small size limit this model. We determined whether human cadaver skin xenografts transplanted onto pigs with severe combined immune deficiency (SCID) would survive and not be rejected. Meshed (1:1.5), cryopreserved human cadaver skin was transplanted onto 10 partial thickness dermatome wounds in each of two normal domestic pigs and two SCID pigs. Autografts ( n = 2/animal) from the four animals were used as controls. In normal pigs, all autografts were engrafted and healed with a minimal, if any, inflammation and scarring. All human xenografts were rejected by the normal pigs within 5–11 days and associated with an intense T‐cell inflammatory response. In contrast, both autografts and xenografts were engrafted and survived the 28‐day study in the SCID pigs with a minimal inflammation and no gross scarring.